Strategy Formulation For Barber Pop - Suparyadi, Bunga Anggriani; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
A survey conducted by â€œChannel News Asiaâ€ in 2011 declares Bandung to be one of top five most creative city in Asia. Therefore, it is not surprising that Bandung city became a source of creative businesses. Creative business todays not only limited to the goods sectors but also entered the service sector such as done by Barber Pop, which entered barbershop industry. The presence of Barber Pop has made a breakthrough in the industry. Unlike other barbershops, Barber Pop strives for excellent customer satisfaction by offering outstanding services while still retaining the traditional concept of a barbershop. The services that offered by Barber Pop has been favored by urban male in Bandung city. This was proven by the number of Barber Pop customers continues to increase every month since the opening of the Barber Pop by July 2011 which causing long waiting list. Based on these facts, the owners has intention to grew their business. However, after performing an analysis, there are internal problems faced by Barber Pop that can be an obstacle for Barber Pop in developing its business such as customersâ€™ dependence on specific barber, unfix schedule of barbersâ€™ holiday, and also the limited capacity provided in current shop. The objective of this final project is to provide suitable strategies for Barber Pop in corporate, business, and functional level of the company in order to help Barber Pop to maintain and grow its presence. The recommended strategy as solution of Barber Pop current condition is that Barber Pop should opening new branch immediately with the same concept using differentiation strategy and fixing any shortcoming in internal condition by hiring public relation, creating barbersâ€™ portfolio, and also create incentive in order to increase barber level of discipline. The implementation of the strategies that were formulated, involve all the internal side of the company such as the marketing, financial, human resource, and operation departments. These strategies need to be monitoring and assessing because they will affect the company future conditions. Therefore a strategy measurement also provided in this final project to know whether the implemented strategy could achieve its target or not.Key Words: service industry, barbershop business, growth strategy